Associated autoimmunity in Type 1 Diabetes and latent autoimmune diabetes of adults: The role of glutamic-acid decarboxylase autoantibodies. (May 2021) - Gougourelas, Dimitrios; Tsentidis, Charalampos; Koufadaki, Athina Maria; Koutsovasilis, Anastasios; Gougourela, Eupraxia; Karanasios, Spyridon; Sotiropoulos, Alexios; Bousboulas, Stavros; Karavanaki, Kyriaki Athina
Abstract: Aims: To determine the prevalence of Associated Autoimmune Diseases (AADs) in Latent Autoimmune Diabetes of Adults (LADA) versus autoimmune Type 1 Diabetes (T1D) and the role of glutamic-acid decarboxylase antibodies (GADA) and other factors. Methods: Adults with autoimmune diabetes mellitus (DM) were recruited from the Diabetes Center of Nikaia-Piraeus Hospital. Demographic and clinical parameters were recorded and anti-pancreatic and organ-specific antibodies were measured. Results: Of 160 patients, 33.75% had one AAD and 24.37% had two or more. Patients with LADA had higher overall prevalence of AADs, mainly autoimmune thyroiditis and gastritis. Celiac disease was present only in T1D. GADA positive patients had higher prevalence of AADs and multiple autoimmunity, especially thyroiditis and gastritis. Patients with LADA had higher rates of positive GADA or islet-cell antibodies (ICA). After controlling for LADA, GADA remained a significant predictor of AADs. Female gender and chronological age were also significant predictors of AADs. Conclusions: AADs were present in 58.13% of patients. Patients with LADA were more prone to a generalized autoimmune disorder than those with T1D. AADs development was significantly associated with female sex, older age and positive GADA, which proved an independent marker of associated autoimmunity.